A Single Amino Acid Mutation in the PA Subunit of the Influenza Virus RNA Polymerase Inhibits Endonucleolytic Cleavage of Capped RNAs - Fodor, Ervin (American Society for Microbiology, 2002)
The influenza A virus RNA-dependent RNA polymerase consists of three subunits—PB1, PB2, and PA. The PB1 subunit is the catalytically active polymerase, catalyzing the sequential addition of nucleotides to the growing RNA chain. The PB2 subunit is a cap-binding protein that plays a role in initiation of viral mRNA synthesis by recruiting capped RNA primers. The function of PA is unknown, but previous studies of temperature-sensitive viruses with mutations in PA have implied a role in viral RNA replication. In this report we demonstrate that the PA subunit is required not only for replication but also for transcription of viral RNA. We mutated evolutionarily conserved amino acids to alanines in the C-terminal region of the PA protein, since the C-terminal region shows the highest degree of conservation between PA proteins of influenza A, B, and C viruses. We tested the effects of these mutations on the ability of RNA polymerase to transcribe and replicate viral RNA. We also tested the compatibility of these mutations with viral viability by using reverse-genetics techniques. A mutant with a histidine-to-alanine change at position 510 (H510A) in the PA protein of influenza A/WSN/33 virus showed a differential effect on transcription and replication. This mutant was able to perform replication (vRNA→cRNA→vRNA), but its transcriptional activity (vRNA→mRNA) was negligible. In vitro analyses of the H510A recombinant polymerase, by using transcription initiation, vRNA-binding, capped-RNA-binding, and endonuclease assays, suggest that the primary defect of this mutant polymerase is in its endonuclease activity.